Citra Merek, Kualitas Produk, dan Content Marketing : Pengaruhnya terhadap Pembelian Produk Calzara Tasikmalaya pada TikTok Shop - Puput Puji Lestari; Azizah Fauziyah; Ismail Yusuf (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Amidst the fierce competition in the digital footwear market, Calzara, an MSME based in Tasikmalaya, faces challenges in sustaining sales performance on the TikTok Shop platform. Consequently, a thorough understanding of the factors that shape consumer purchasing behavior is essential. This study specifically examines the influence of three key variables—brand image, product quality, and content marketing strategies—on purchase decisions for Calzara products. The research employs a quantitative methodology with a descriptive-verificatory design, involving 91 consumers selected through simple random sampling. Data collected via online questionnaires were analyzed using multiple linear regression. The primary findings reveal that these three variables collectively explain 57.1% of the variance in purchase decisions, with the remaining 42.9% likely influenced by other factors outside the scope of this study’s model. These results provide valuable insights for Calzara to optimize its brand image, enhance product quality, and develop more effective content marketing strategies to drive consumer purchase decisions on the TikTok Shop platform.